An Integrated Resilience and Life Skills (IRLS) Framework for Adolescent Development: Synthesizing Theory, Practice, and Digital Innovation - Lissamol T George; Dr. Mansi Kapoor (Supervisor) (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Adolescence is a critical developmental period marked by heightened exposure to academic, social, identity-related, and digital stressors, with enduring implications for mental health and well-being. Although scholarship on adolescent well-being, resilience, and life skills has expanded substantially, these literatures remain conceptually fragmented, limiting understanding of how teachable competencies support adaptive development. This paper introduces the Integrated Resilience and Life Skills (IRLS) Framework, an integrative conceptual model that clarifies the mechanisms linking life skills, coping processes, resilience, and well-being in adolescence, while explicitly incorporating digital literacy as a developmentally salient competency. Using a structured narrative (integrative) review and theory-synthesis approach, peer-reviewed literature published between 2000 and 2025 on adolescent well-being, resilience, life skills, coping, and digital literacy was examined to identify recurring constructs and relational patterns. The synthesis identified emotional regulation, problem-solving, decision-making, and interpersonal communication as core, modifiable life skills supporting adaptive coping, with enactment shaped by external supports across family, school, peer, and community systems. Digital literacy emerged as a cross-cutting competency moderating how adolescents apply cognitive, emotional, and social skills in digitally mediated contexts. The IRLS Framework advances existing models by specifying skill-based mechanisms of resilience and situating adolescent development within contemporary digital environments, providing a unifying structure to guide future research, intervention design, and policy efforts, while underscoring the need for longitudinal and cross-cultural empirical validation.